[6+3] cycloaddition of fulvenes with 3-oxidopyrylium betaine: a novel methodology for the synthesis of fused cyclooctanoid natural products - Radhakrishnan, K. V.; Krishnan, K. Syam; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Tetrahedron Letters, 2005)
Fulvenes undergo an easy [6+3] cycloaddition with 3-oxidopyrylium betaines leading to 5-8 fused oxabridged cyclooetanoids. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cyclooctanoids; fulvenes; oxidopyrylium betaines; [6+3] cycloaddition

Benzoyl transfer reactivities of racemic 2,4-Di-O-acyl-myo-inosityl 1,3,5-orthoesters in the solid state: molecular packing and intermolecular interactions correlate with the ease of the reaction - Sarmah, M. P.; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2005)
Racemic 2,4-di-O-acyl-myoinosityl 1,3,5-orthoesters undergo transesterification catalyzed by sodium carbonate with varying ease of reaction in the solid state; reactions in solution and melt do not show such varied differences. An interesting crystal of a 1:1 molecular complex of highly reactive racemic 2,4-di-O-benzoyl-myo-inosityl 1,3,5-orthoformate and its orthoacetate analogue exhibited better reactivity than the latter component alone. Single-crystal X-ray structures of the reactants have been correlated with the observed differences in the acyl-transfer efficiencies in the solid state. Although each of the derivatives helically self-assembles around the crystallographic 2(1) axis linked through O-(HO)-O-... hydrogen bonding, the pre-organization of the reactive groups (C=O [El] and OH [Nu]), C-(HO)-O-... and the C=H(...)pi interactions are significantly more favourable for the reactive derivatives than the less reactive ones. Bond-length distributions also showed differences; the O-C bond of the axial benzoyl group, which gets cleaved during the reaction, is longer (1.345-1.361 angstrom) relative to the chemically equivalent O-C bond of the equatorial benzoyl group (1.316-1.344 angstrom) in the reactive derivatives. These bond-length differences are not significant in the less reactive derivatives. The overall molecular organization is different too; the strikingly discrete helices, which may be viewed as ``reaction tunnels'' and are held by interhelical interactions, are clearly evident in the reactive derivatives in comparison with the less reactive ones.
Keywords: hydrogen bonds; Inositol; solid-state reactions; structure elucidation; transesterification

Concomitant dimorphs of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates with different halogen bonding contacts: first order crystal-to-crystal thermal phase transition of kinetic form to the thermodynamic form - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S.; Sanki, A. K. (Chemical Communications, 2005)
Crystallization of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates from ethyl acetate-petroleum ether solution produced concomitant dimorphs that have different halogen bonding contacts; the kinetic form with C-(BrO)-O-...-C contacts upon heating to 185 degrees C, converts completely to the thermodynamic form with C-(BrOLC)-O-... contacts via crystal-to-crystal first order phase transition.

Efficient method for the synthesis of methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate - Salunke, D. B.; Hazra, Braja G.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Pore, V. S. (Tetrahedron, 2005)
The synthesis of methyl 11 alpha-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate, methyl 11 beta-azido-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate and methyl 11 alpha-amino-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate have been achieved. Mechanistic aspects for the decomposition of steroidal azidoketones to its enamines are discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 11-aminosteroid; 11-azidosteroid; base catalyzed epimerization; HIV-1 protease inhibitors; steroidal enamines

First enantiospecific synthesis of (+)-beta-herbertenol - Chavan, Subhash P.; Thakkar, M.; Kharul, Rajendra K.; Pathak, A. B.; Bhosekar, Gaurav V.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
The first enantiospecific synthesis of (+)-beta-herbertenol, from naturally occurring R-(+)-citronellal, employing Taber's diazo decomposition protocol as the key step, is described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: citronellal; diazo decomposition; enantiospecific

Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

Isolation and characterization of an iodide bridged dimeric palladium complex in carbonylation of methanol - Tonde, S. S.; Kelkar, Ashutosh A.; Bhadbhade, Mohan M.; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2005)
Palladium-catalyzed carbonylation of methanol in presence of iodide promoters was investigated. Iodide bridged palladium dimeric complex, [PPh3CH3](2)[Pd2I6] was isolated from the carbonylation reaction mixture and characterized using X-ray crystallography. Reaction mechanism was proposed based on IR and UV spectroscopic characterizations of catalytic species involved in the catalytic cycle. The isolated dimeric palladium species, [Pd2I6](2-) underwent carbonylation to give monomeric species [PdI3CO](-) at atmospheric pressure of carbon monoxide. It was also observed that PPh3 plays an important role to avoid catalyst deactivation at higher temperatures. Turnover frequency (TOF) of 1052 h(-1) was achieved using Pd(OAC)(2)-HI-PPh3 catalyst system at 175 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dirneric palladium; IR spectroscopy; methanol carbonylation; palladium catalyst; reaction mechanism; UV

Metalloantitubercular compounds part 3: synthesis, crystal structure, spectroscopy, electrochemistry and antimycobacterial activity of the copper(II) ciproploxacin (cfH) complex and its phenanthroline adduct - Saha, D. K.; Patitungkho, S.; Padhye, S.; Deobagkar, D. N.; Ozarkar, A.; Bhadbhade, Mohan M.; Gonnade, Rajesh G. (Transition Metal Chemistry, 2005)
The X-ray crystal structures of two ciprofloxacin compounds, viz. [Cu(cfH)(2)(Cl)(2)] (.) 2MeOH (.) 6H2O (2) and [Cu(cfH)(phen)Cl]BF4 (.) 4H(2)O (3) are reported. Complex ( 2) has a distorted octahedral geometry, whereas for the nitrogen adduct (3) a distorted square-pyramidal geometry is seen. Significant enhancement in the antimycobacterial activity of the copper conjugates correlates with their copper redox couples (Cu2+/Cu+) probably due to its relevance to intracellular accumulations and subsequent role in generating oxidative stress.

New bis-andrographolide ether from androgphis paniculata nees and evaluation of anti-HIV activity - Reddy, V. L. N.; Reddy, S. M.; Ravikanth, V.; Krishnaiah, P.; Goud, T. V.; Rao, T. P.; Ram, T. S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Venkateswarlu, Y (Natural Product Research, 2005)
Novel bis-andrographolide ether (1) and six known compounds andrographolide, 14-deoxy-11,12-didehydroandrographolide, andrograpanin, 14-deoxyandrographolide, (+/-)-5- hydroxy-7,8-dimethoxyflavanone, and 5-hydroxy-7,8-dimethoxyflavone have been isolated from the aerial parts of Andrographis paniculota and their structures were established by spectral data. All the isolates were tested for the anti-HIV and cytotoxic activity.
Keywords: Acanthaceae; Andrographis paniculata; anti-HIV; bis-andrographolide ether; Cytotoxic activity

O-H center dot center dot center dot O-bridged dimers linked via C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions in 4,6-di-O-benzyl-myo-inositol 1,3,5-orthoformate - Manoj, Kochunnoonny; Devaraj, Subramanian; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2005)

Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.

Sulfonate protecting groups. synthesis of O- and C-methylated inositols: D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether - Sarmah, M. P.; Shashidhar, M. S.; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
Syntheses of D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether starting from myo-imositol are described. One or two of the inyo-inositol 1,3,5-orthoformate hydroxyl groups were protected as tosylates. These mono or ditosylates served as key intermediates for the preparation of O- and C-methyl inositols. Racemic 2,4-di-O-tosyl-myo-inositol 1,3,5-orthoformate was resolved as its diastereomeric camphanates. Use of sulfonate groups for the protection of inositol hydroxyl groups resulted in substantial improvement in the overall yield of O- and C-methyl inositols. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Orthoester; Protecting group; sulfonate

Synthesis and intramolecular nitrile oxide cycloaddition of 3,5 `-ether-linked pseudooligosaccharide derivatives: an approach to chiral macrooxacycles - Sengupta, J.; Mukhopadhyay, R.; Bhattacharjya, A.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Journal of Organic Chemistry, 2005)
[GRAPHIC] 3,5'-Ether-linked pseudooligopentose derivatives were synthesized for the first time from readily available carbohydrate precursors. The 1,2-isopropylidene-protected ether-linked oligopentoses are potentially important as precursors of novel RNA analogues. Intramolecular cycloaddition of the nitrile oxides prepared from these derivatives led to the diastereoselective formation of chiral isoxazolines fused to 10-16-membered oxacycles. The stereochemistry of some of these isoxazolines was established by X-ray diffraction and NOESY analysis.

[6+3] cycloaddition of pentafulvenes with 3-oxidopyrylium betaine: a novel methodology toward the synthesis of 5-8 fused oxabridged cyclooctanoids - Krishnan, K. Syam; Sajisha, V. S.; Anas, S.; Suresh, C. H.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V.; Radhakrishnan, K. V. (Tetrahedron, 2006)
Pentafulvenes undergo a facile [6+3] cycloaddition with 3-oxidopyrylium betaine, generated from the corresponding pyranulose acetate, leading to the formation of 5-8 fused oxabridged cyclooctanoids. The product is formed by a [6+3] cycloaddition, followed by a 1,5-hydrogen shift of the initially formed [6+3] adduct. The reaction was found to be general and a number of fulvenes with a wide range of substituents at the exocyclic double bond, that is, at the C6 position followed a similar reactivity pattern. The [6+3] adduct, a 5-8 fused oxabridged cyclooctanoid, is potentially amenable to a number of synthetic transformations due to the presence of an alpha, beta-unsaturated ketone and cyclopentadiene part. By selecting appropriately substituted fulvene and pyranulose acetates, it is possible to use this methodology for the synthesis of a wide range of 5-8 fused cyclooctanoids. The experimental results have been rationalized on the basis of theoretical calculations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: fulvenes; oxabridged cyclooctanoids; oxidopyrylium betaine; [6+3] cycloaddition

Cu(I)-catalyzed cycloaddition of constrained azido-alkynes: access to 12- to 17-membered monomeric triazolophanes incorporating furanoside rings - Ray, A.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mukhopadhyay, R.; Bhattacharjya, A. (Tetrahedron Letters, 2006)
A strained monomeric 12-membered triazolophane was formed by the Cu(I)-catalyzed intramolecular cycloaddition of an azide to an alkyne having a constrained tether incorporating ail aromatic ring and a furanoside ring. Similar cycloadditions of azido-alkynes having ester, furanoside and peptidic tethers led to the formation of monomeric triazolophanes of higher ring sizes. (c) 2006 Elsevier Ltd. All rights reserved.

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Different interaction motifs of dipolar S = O center dot center dot center dot C = O contacts that associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-7,7-dimethyl-2-oxo-bicyclo[2.2.1]heptan-1-ylmethyl]-sulfonyl-myo-inositol 1,3,5-ortho-acetate - Manoj, Kochunnoonny; Gonnade, R. G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C‐Structural Chemistry, 2007)
Diastereomeric mixtures of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoesters associate in their crystal structures via different geometries of S=O...C=O short contacts, depending upon the substitution. A comparison of the dimeric association in the orthoacetate and orthoformate (solvated) derivatives shows a sheared parallel motif of dipolar S=O...C=O contacts bridging the former, whereas perpendicular S=O...C=O contacts occur in the latter. The title compound, C32H34O11S, is chiral, owing to the presence of the camphor moiety.

Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C

Ferrocene-linked thymine/uracil conjugates: base pairing directed self-assembly and supramolecular packing - Patwa, Amit N.; Gupta, Susmita; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2008)
Ferrocene-linked bis(nucleobase) (la-c) and chimeric nucleobase (1d) conjugates have been synthesized from mono- and bis(hydroxybutyl)ferrocene 6 via Mitsunobu reaction as the key step. X-ray crystallographic studies of ferrocene bis(nucleobase) conjugates reveal two-dimensional supramolecular organizations of backbones through self-assembled Watson-Crick and reverse Watson-Crick type pairs. Ferrocene-bis(thymine) conjugate self-assembles by reverse Watson-Crick pairing, while the corresponding bis(uracil) conjugate self-assembles by alternating WC and reverse WC type pairing. Such continuous assemblies are not seen in monosubstituted ferrocene nucleobase conjugates which form only planar sheets. The results are interesting from the point of understanding and engineering supramolecular assemblies through rational design of base pairing patterns.

Molecular association via halogen bonding and other weak interactions in the crystal structures of 11-bromo-12-oxo-5 beta-cholan derivatives - Salunke, Deepak B.; Hazra, Braja G.; Gonnade, Rajesh G.; Pore, Vandana S.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Methyl 3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 2, methyl 11 alpha-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 3, methyl 11 beta-bromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 4 and methyl 11,11-dibromo-3 alpha,7 alpha-diacetoxy-12-oxo-5 beta-cholan-24-oate 5 were synthesized. The crystal structures of these molecules were resolved to study the effect of bulky bromine atom in the steroid skeleton of cholic acid with different stereo-chemical orientations at C-11 on the two-dimensional arrangement of molecules and solid-state properties. All the molecules associate only via weak intermolecular interactions in their crystal structures, notable one being the Halogen Bonded assembly (C-Br center dot center dot center dot O) in 5. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 11-Bromosteroids; Cholic acid; crystal structure; Halogen bonding

Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations

Dipolar S=O center dot center dot center dot C=O and C-H center dot center dot center dot O interactions in the molecular organization of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
In the absence of conventional hydrogen bonding, the molecules of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoformate, C(18)H(20)O(10)S, (I), and 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthobenzoate, C(24)H(24)O(10)S, (II), are associated via C-H center dot center dot center dot O interactions. Molecules of (II) are additionally linked via dipolar S=O center dot center dot center dot C=O contacts. It is interesting to note that the sulfonyl O atom involved in the dipolar S=O center dot center dot center dot C=O contacts does not take part in any other interaction, indicating the competitive nature of this contact relative to the weak hydrogen-bonding interactions.

Enhancing intermolecular benzoyl-transfer reactivity in crystals by growing a ``reactive'' metastable polymorph by using a chiral additive - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2009)
Racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate, which normally crystallizes in a monoclinic form (form I, space group P2(1)/n) could be persuaded to crystallize out as a metastable polymorph (form II, space group C2/c) by using a small amount of either D- or L- 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate as an additive in the crystallization medium. The structurally similar enantiomeric additive was chosen by the scrutiny of previous experimental results on the crystallization of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoacetate. Form II crystals call be thermally transformed to form I crystals at about 145 degrees C. The relative organization of the molecules in these dimorphs vary slightly in terms of the helical assembly of molecules, that is, electrophile (El)center dot center dot center dot nucleophile (Nu) and C-H center dot center dot center dot pi interactions, but these minor variations have a profound effect on the facility and specificity of benzoyl-group-transfer reactivity in the two crystal forms. While form II crystals undergo a clean intermolecular benzoyl-group-transfer reaction, form I crystals are less reactive and undergo non-specific benzoyl-group transfer leading to a Mixture of products. The role played by the additive in fine-tuning small changes that are required in the molecular packing opens up the possibility of creating new polymorphs that show varied physical and chemical properties. Crystals of D-2.6-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (additive) did not show facile benzoyl-group-transfer reactivity (in contrast to the corresponding racemic compound) due to the lack of proper juxtaposition and assembly of molecules.
Keywords: Acylation; carbohydrates; Crystal growth; cyclitols; solid-state reactions

Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.

Two modes of O-H center dot center dot center dot O hydrogen bonding utilized in dimorphs of racemic 6-O-acryloyl-2-O-benzoyl-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
The title compound, C(17)H(16)O(8), yields conformational dimorphs [forms (I) and (II)] at room temperature, separately or concomitantly, depending on the solvent of crystallization. The yield of crystals of form (I) is always much more than that of crystals of form (II). The molecule has one donor -OH group that can make intermolecular O-H center dot center dot center dot O hydrogen bonds with one of the two acceptor C O groups, as well as with the hydroxyl O atom; interestingly, each of the options is utilized separately in the dimorphs. The crystal structure of form (I) contains one molecule in the asymmetric unit and is organized as a planar sheet of centrosymmetric dimers via O H center dot center dot center dot O hydrogen bonds involving the OH group and the carbonyl O atom of the acryloyl group. In the crystal structure of form (II), which contains two independent molecules in the asymmetric unit, two different O-H center dot center dot center dot O hydrogen bonds, viz. hydroxyl-hydroxyl and hydroxyl-carbonyl (benzoyl), connect the molecules in a layered arrangement. Another notable feature is the transformation of form (II) to form (I) via melt crystallization upon heating to 411 K. The higher yield of form (I) during crystallization and the thermal transition of form (II) to form (I) suggest that the association in form (I) is more highly favoured than that in form (II), which is valuable in understanding the priorities of molecular aggregation during nucleation of various polymorphs.

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.

Ferrocene-Bis(thymine/uracil) conjugates: base pairing directed, spacer dependent self-assembly and supramolecular packing - Patwa, Amit N.; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2010)
X-ray crystallographic studies of methylene linked Ferrocene-bis(thymine/uracil) conjugates Fc(T:T)m and Fc(U:U)(M) reveal base dependent 2-D supramolecular assemblies generated via wobble self-pairing for bis-thymine and reverse wobble self-pairing for bis-uracil conjugates, differing in architecture from the corresponding butylene spacer linked conjugates

Helical self-assembly of molecules in pseudopolymorphs of racemic 2,6-di-O-(4-halobenzoyl)-myo-inositol 1,3,5-orthoformates: clues for the construction of molecular assemblies for intermolecular acyl transfer reaction - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2010)
The crystal structure of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate (1) which underwent a facile intermolecular benzoyl transfer reaction in the solid state, revealed a helical assembly of molecules along the two-fold screw axis via O-H center dot center dot center dot O hydrogen bond bringing the electrophile (C=O) and the nucleophile (-OH) in close proximity along the helical axis. However, structurally related racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (2) and chloro (3)) produced triclinic dimorphs (both P (1) over bar) when crystallized from methanol and ethyl acetate. Molecules in either form did not assemble spirally (like 1), and instead exhibited a one-dimensional isostructurality, bridging O-H center dot center dot center dot O linked identical molecular strings via C-H center dot center dot center dot O interactions across the inversion center. However, the molecules of 2 and 3 assembled in a helical manner similar to 1 with inclusion of solvent molecules in the crystal lattice when crystallized from other common organic solvents. Remarkably, in all the solvates the host molecules formed strikingly similar helices around the crystallographic 2(1)-screw axis through O-H center dot center dot center dot O bond involving the -OH group and carbonyl oxygen of the equatorial C2-O-benzoyl group. Comparison of the crystal structure of dimorphs and the solvatomorphs revealed that the solvent molecules, which interact with the orthoformate-bridge, trigger the helix formation of the host. The difference in the crystal structures of solvatomorphs arises in the interlinking of the neighbouring helices, which creates voids of different sizes to accommodate the solvent molecules. All the solvates crystallized in the monoclinic system distributed over three different space groups P2(1)/n, P2(1)/c and C2/c. In the P2(1)/n system, the adjacent helices are linked via C-X center dot center dot center dot O contacts, in P2(1)/c via C-H center dot center dot center dot X (X Cl, Br) contacts and in C2/c via short X center dot center dot center dot X contacts (X = Cl). The helical organization achieved through solvent mediation and inclusion is of significance in creating molecular packing for intermolecular acyl transfer reactions in crystals.

Syntheses, characterisation and vapour pressure of metallo-organic titanium precursor for MOCVD applications - Arockiasamy, S.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mallika, C.; Nagaraja, K. S. (Inorganica Chimica Acta, 2010)
Metallo-organic complexes of titanium such as [Ti(bzac)(2)(O(i)Pr)(2)] (1) and [Ti(bzac)(2)en(O(i)Pr)(2)] (2) were synthesised using 1-phenyl-1,3-butanedione (bzac) and the Schiff's base ligand N, N0-ethylene-bis(1-phenyl-1,3-butanediimine) [(bzac)(2)en]. A novel ligand 1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanone (bzac1a2pol, 3) synthesised by condensing benzoylacetone (bzac) with 1-amino-2-propanol (1a2pol) was used in the synthesis of the complex bis(1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanoato)titanium (IV), [Ti(bzac1a2pol)(2), 4]. These complexes were synthesised by replacing the isopropoxy group (O(i)Pr) of titanium tetra-isopropoxide, Ti(O(i)Pr)(4) by the appropriate ligands. Complexes 1, 2 and 4 were characterised for their volatility/thermal stability using TG/DTA and complex 4 was found to be volatile giving a residue of similar to 5.0% (TG) at 377 degrees C and similar to 3.0% (reduced pressure, 1 mbar) at 285 degrees C. Ligand 3 and its Ti complex 4 were characterised by (1)H NMR, (13)C NMR, elemental analysis, mass spectrometry and single crystal XRD. A value of 164.2 +/- 5.2 kJ mol(-1) for the standard enthalpy of sublimation (Delta H(sub)(0)) was evaluated for 4 from its vapour pressure. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: MOCVD; Single crystal; Syntheses; Ti complexes; Vapour pressures; Volatile complexes

Halogen bonding in 2,5-dichloro-1,4-benzoquinone: insights from experimental and theoretical charge density analysis - Hathwar, Venkatesha R.; Gonnade, Rajesh G.; Munshi, Parthapratim; Bhadbhade, Mohan M.; Row, Tayur N. Guru (Crystal Growth & Design, 2011)
Experimental charge density distribution in 2, 5-dichloro-1, 4-benzoquinone has been carried out using high resolution X-ray diffraction data at 90 K to quantitatively evaluate the nature of C-Cl center dot center dot center dot O=C halogen bond in molecular crystals. Additionally, the halogen bond is studied from geometrical point of view and the same has been visualized using Hirshfeld surface analysis. The obtained results from experimental charge density analysis are compared with periodic quantum calculations using B3LYP 6-31G(d,p) level of theory. The topological values at bond critical point, three-dimensional static deformation density features and electrostatic potential isosurfaces unequivocally establish the attractive nature of C-Cl center dot center dot center dot O=C halogen bond in crystalline lattice.

Intermolecular benzoyl group transfer reactivity in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate: controlling reactivity by solvate (pseudopolymorph) formation - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2011)
Racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate (rac-3), which usually crystallizes in a monoclinic lattice (Form I, P2(1)/c) from common organic solvents, when crystallized from 2-propanol yielded concomitantly, thin whisker like crystals (Form II, triclinic, P (1) over bar) with inclusion of 2-propanol and water molecules, along with the Form I crystals. Thin fibre-like crystals were also obtained on crystallization from toluene, with inclusion of toluene and water in the crystal lattice (Form III). The Form II and Form III crystals could be converted into the Form I crystals thermally via melt crystallization. Form I crystals exhibit a facile transesterification reaction, but the solvated crystals are unreactive under the same conditions until their transformation to the reactive form. The reactivity patterns of the Form I and Form II crystals correlate well with the molecular organization in them. Since reactivity of the crystals of rac-3 depends on the solvent and the method of crystallization, and the thermal transition of one crystal form to the other, these phase changes can be used as a switch to control the benzoyl transfer reactivity of the constituent molecules in crystals.

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Helical preorganization of molecules drives solid-state intermolecular acyl-transfer reactivity in crystals: structures and reactivity studies of solvates of racemic 2,6-Di-O-(4-fluorobenzoyl)-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2017)
Racemic 2,6-di-O-(4-fluorobenzoyl)-myo-inositol 1,3,5-orthoformate yielded structurally dissimilar solvent-free and solvated crystals depending upon the solvent of crystallization. The solvated crystals exhibited helical assembly of host molecules, due to the interaction of the guest molecules with the orthoformate moiety of the host. Some of the solvates showed specific but incomplete benzoyl group transfer reactivity below the phase transition temperature, whereas the reaction in solvent-free crystals led to a mixture of several products. These results reveal the necessity of helical molecular packing of the reacting molecules in their crystals to facilitate specific intermolecular acyl transfer reactivity. The crystal, structures of the fluorobenzoate solvates were similar to those of the solvates of the analogous chloro and bromobenzoates. The latter could be thermally :transformed into their solvent-free form via melt crystallization, resulting in the conversion of a helical molecular packing into a nonhelical molecular packing.